Compact Dual-Band Dipole Antenna with Asymmetric Arms for WLAN Applications - Chung-Hsiu Chiu; Chun-Cheng Lin; Chih-Yu Huang; Tsai-Ku Lin (International Journal of Antennas and Propagation)
A dual-band dipole antenna that consists of a horn- and a C-shaped metallic arm is presented. Depending on the asymmetric arms, the antenna provides two −10 dB impedance bandwidths of 225 MHz (about 9.2% at 2.45 GHz) and 1190 MHz (about 21.6% at 5.5 GHz), respectively. This feature enables it to cover the required bandwidths for wireless local area network (WLAN) operation at the 2.4 GHz band and 5.2/5.8 GHz bands for IEEE 802.11 a/b/g standards. More importantly, the compact size (7 mm × 24 mm) and good radiating performance of the antenna are profitable to be integrated with wireless communication devices on restricted RF-elements spaces.